2010 IEEE International Conference on Communications 2010
DOI: 10.1109/icc.2010.5502824
|View full text |Cite
|
Sign up to set email alerts
|

Variance-Aware Adaptive Modulation for OFDM-Based Multiple Description Progressive Image Transmission

Abstract: Average throughput maximization has commonly been used as an alternative to image or video average distortion minimization. However, as the throughput-distortion curve is non-linear, throughput maximization can be very different from distortion minimization if the variance of the throughput is large. Under high channel quality variability, the variance of the throughput will be high. Multiple description coding with unequal error protection is a promising technique for the transmission of progressive images wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Recent works demonstrated that, when the priority of the encoded bitstream is taken into account in the system optimization design, the overall performance can considerably increase. In [10], joint adaptive channel coding and multiple description coding for progressive image transmission over orthogonal frequency division multiplexing (OFDM) systems were investigated both for fixed and for adaptive modulation. Note that, the payload priority was considered in the channel coding across the subcarriers and not in the modulation scheme, which was investigated in [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent works demonstrated that, when the priority of the encoded bitstream is taken into account in the system optimization design, the overall performance can considerably increase. In [10], joint adaptive channel coding and multiple description coding for progressive image transmission over orthogonal frequency division multiplexing (OFDM) systems were investigated both for fixed and for adaptive modulation. Note that, the payload priority was considered in the channel coding across the subcarriers and not in the modulation scheme, which was investigated in [11].…”
Section: Introductionmentioning
confidence: 99%